Sistem Pendukung Keputusan Pemberian Potongan Harga Pada Toko Bangunan Dunia Baru Menggunakan Metode SMARTER - Triana Elizabeth; Tinaliah Tinaliah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Discounts are one of the marketing strategies used by Dunia Baru Store as a solution for decreasing sales for the last 3 years. Staff employees have difficulty in providing discounts to the right customer and difficulty knowing the amount of discount that is suitable for that customer. The Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) method is one of the decision-making methods for granting discounts where each alternative has criteria that have weights obtained from using the Rank Order Centroid (ROC) weighting formula on each criterion and sub-criteria. There are 4 criteria used, namely the number of purchases, purchase intensity, buyer attitudes, and delivery methods. The number of purchases and purchase intensity are obtained from the sales application and material stock, while the buyer's attitude and delivery method are inputted directly by the staff. A decision-making feature that provides information about final grades, rankings, and discounts has helped the owners and staff of the Dunia Baru Store in providing discounted recommendations to the right customers.